Peranan Dinas Sosial dalam Menangani Masalah Kekerasan Sosial Terhadap Anak di Provinsi Sumatera Utara - Dwi Putri Rachmawati; Syafruddin Ritonga; Beby Masitho Batubara (Universitas Medan Area, 2020)
The role of the Office of Social Affairs in addressing the problem of sexual violence against children as a place to provide public complaints about the problem and duty to help resolve the problem. A child is a person under 17 years of age and unmarried, where the child is someone who must be protected, nurtured and fostered to achieve prosperity. Sexual violence is a real action related to intimacy or sexuality that results in victims suffering physically, materially, mentally, or psychologically. In its role in overcoming the problem of sexual violence against children, the Social Service is tasked with assisting victims, witnesses, and perpetrators who are still children from the investigation stage to the trial. The social service also has obstacles in solving the problem of sexual violence against children in the form of budget problems and sectoral ego. In this study the method that researchers take is qualitative research methods